Promoting access to and use of seismic data in a large scientific community - Michel Eric; Belkacem Kevin; Samadi Reza; Assis Peralta Raphael de; Renié Christian; Abed Mahfoudh; Lin Guangyuan; Christensen-Dalsgaard Jørgen; Houdek Günter; Handberg Rasmus; Gizon Laurent; Burston Raymond; et al. (EPJ Web of Conferences, 2017)
The growing amount of seismic data available from space missions (SOHO, CoRoT, Kepler, SDO,…) but also from ground-based facilities (GONG, BiSON, ground-based large programmes…), stellar modelling and numerical simulations, creates new scientific perspectives such as characterizing stellar populations in our Galaxy or planetary systems by providing model-independent global properties of stars such as mass, radius, and surface gravity within several percent accuracy, as well as constraints on the age. These applications address a broad scientific community beyond the solar and stellar one and require combining indices elaborated with data from different databases (e.g. seismic archives and ground-based spectroscopic surveys). It is thus a basic requirement to develop a simple and effcient access to these various data resources and dedicated tools. In the framework of the European project SpaceInn (FP7), several data sources have been developed or upgraded. The Seismic Plus Portal has been developed, where synthetic descriptions of the most relevant existing data sources can be found, as well as tools allowing to localize existing data for given objects or period and helping the data query. This project has been developed within the Virtual Observatory (VO) framework. In this paper, we give a review of the various facilities and tools developed within this programme. The SpaceInn project (Exploitation of Space Data for Innovative Helio- and Asteroseismology) has been initiated by the European Helio- and Asteroseismology Network (HELAS).